Developing a Social Network of Support to Health Care: The Experience of GenNet - Magalhães, Cleyton; Santos, Ronnie; Correia Neto, Jorge S.; Vilar, Guilherme (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Based on the context in which social networks and collaborative systems are involved, this paper presents the process of conception, projection and implementation of a collaborative social network with the goal to promote actions related to social inclusion of people with genetic disorders with physical disabilities. Using an experimental and descriptive approach the creation and development of GenNet is described and reflections are made over the particularities of this process in the healthcare environment.